Penerapan Model Pengajaran Tuntas untuk Meningkatkan Prestasi Belajar Siswa dalam Pelajaran Pendidikan Agama Katolik Pada Siswa Kelas XI SMK Negeri 3 Jayapura - Maksilianus Mena (Sekolah Tinggi Katolik Touye Paapaa Deiyai, 2024)
This study aims to evaluate the effectiveness of the completed teaching model in improving students' understanding of church social teaching materials. The completed teaching model is implemented through an approach that ensures each student reaches the expected level of understanding before moving on to the next material. This study used a quantitative method with an experimental design. Data were collected through learning achievement tests, classroom observations, and interviews with students and teachers. The results showed a significant increase in students' learning achievement after the implementation of the completed teaching model. Students showed a deeper understanding of church social teachings and were able to apply the knowledge in the context of daily life. In addition, this model also increased students' learning motivation and active participation in the learning process. Thus, the due diligent teaching model is proven effective in improving students' learning achievement in Catholic Religious Education and Cultivation subjects. The recommendation of this research is that the model can be adopted more widely in other subjects to improve the quality of education in schools.